The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.5114/aoms.2011.25547
|View full text |Cite
|
Sign up to set email alerts
|

One more look at guidelines for primary and secondary prevention of cardiovascular disease in women

Abstract: The most common cause of death in menopausal women is due to complications from cardiovascular disease. However, many physicians feel that the prevention in women may be delayed, because women present the clinical manifestations of cardiovascular disease 10 years later than men. Another matter emerged following the results of the Women's Health Initiative study and of the Heart Estrogen/Progestin Replacement Study. Thus the proper interpretation and implementation of science should be included in a strict proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Therefore, concurring Sekuri et al [18] recommendations, strong interventions to significantly reduce CVR among post-menopausal women should be included in routine primary health care programs. As such, these women should receive educational sessions on healthy lifestyles, which revolve around emphasizing regular physical activity, avoiding or stopping smoking, avoiding excessive alcohol consumption, maintaining a normal body weight, and adopting a healthy diet [2,19,20]. Omega-3 fatty acids may be administered in high-risk women, as well as folic acid, vitamin K and vitamin D [19,21,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, concurring Sekuri et al [18] recommendations, strong interventions to significantly reduce CVR among post-menopausal women should be included in routine primary health care programs. As such, these women should receive educational sessions on healthy lifestyles, which revolve around emphasizing regular physical activity, avoiding or stopping smoking, avoiding excessive alcohol consumption, maintaining a normal body weight, and adopting a healthy diet [2,19,20]. Omega-3 fatty acids may be administered in high-risk women, as well as folic acid, vitamin K and vitamin D [19,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, women should be educated on consumption of a healthy diet, i.e. consumption of a variety of fruits, vegetables, cereals, dairy products with low or without fat; consumption of fish, legumes, and proteins with low content of unsaturated fat (poultry, lean meat, plant); restriction of consumption of unsaturated fat (< 10% of total calories), cholesterol (300 mg/ /daily), and trans-fatty acids) [2,19,20]. It is worth emphasizing, however, that diet alone may be unsatisfactory and should therefore be associated with regular physical exercise as it has been shown that diet restriction without exercise may appear inefficient [20,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During aging, there is usually a progressive reduction in physical activity. Although physical training programs are currently part of recommendations for disease prevention and cardiac rehabilitation [58], their effects on LV diastolic function of elderly individuals are still unclear. Most available data have come from studies with elderly who have been involved in sports competitions for periods of at least 10 years [2,4,911].…”
Section: Introductionmentioning
confidence: 99%
“…1 The World Health Organization has defined natural menopause as minimum 12 consecutive months of amenorrhea occurring without any surgical intervention or other pathological causes. 2,3 In the West industrialized populations, the mean ANM is 51 years, and in poor and nonindustrialized populations it is 48 years.…”
mentioning
confidence: 99%